Activation of cannabinoid receptor type 1 impairs spatial and temporal aspects of episodic-like memories in rats - Ko-En Chiang, Yi-Tse Hsiao (Journal of Integrative Neuroscience, 2020)
The endocannabinoid system modulates many brain functions, including episodic memories, which contain memories of time and places. Most studies have focused on the involvement of the endocannabinoid system in spatial memory; however, its role in temporal memory is not well understood. Few studies have tested whether the unilateral endocannabinoid system is sufficient to modulate memory retrieval. Here, we tested whether type 1 cannabinoid receptors in the right hippocampal cornu ammonis area 1 region are enough to modulate the retrieval of episodic memories, specifically their spatial and temporal components. Because rats have innate preferences for displaced or old familiar objects, we changed the locations of "old familiar" and "recent familiar" objects in an open field and measured the rats' exploration times to evaluate spatial and temporal memory. To address the influence of the type 1 cannabinoid receptors on the retrieval of episodic-like memories, two doses of arachidonylcyclopropylamide, a selective type 1 cannabinoid receptor agonist, were infused into the cornu ammonis area 1 of rats ten minutes before the discrimination trials. We observed that rats injected with a low dose of arachidonylcyclopropylamide spent less time investigating displaced objects, suggesting spatial memory impairment, whereas those receiving a high dose explored old familiar objects less frequently, suggesting temporal memory impairment. This indicates that unilateral activation of type 1 cannabinoid receptors in the cornu ammonis area 1 impairs the spatial and temporal aspects of episodic memories. This research mimics the influence of marijuana intoxication effects in humans, such as spatial and temporal disintegration.